PENGAWASAN PADA PELAKSANAAN PROGRAM BANTUAN PEMBANGUNAN TEMPAT IBADAH DI DESA WANGA KECAMATAN MOTOLING TIMUR KABUPATEN MINAHASA SELATAN - LENDO, INDAH LIDIA; LALOMA, ALDEN; ROMPAS, WELSON YAPPI (JURNAL ADMINISTRASI PUBLIK, 2018)
This study aims To find out how the supervision on the implementation of aid programs construction ofplaces of worship in the Village Wanga District Motoling Timur South MinahasaThis research uses descriptive research method with qualitative approach. By applying a qualitativeapproach the authors have a wider opportunity in interacting with the object of research, so as to enrichand deepen the study in research that the author do Data Collection Techniques used some Interviewtechniques, Documentation study, ObservationThe results show the actual performance is smaller than the standard or in other words that what is doneby the development commission in the congregation of GMIM Sion wanga village has not reached asexpectedKeywords: Supervision, Development Assistance Program Place of Worship